Better feed, more income, zero pesticide - International Livestock Research Institute (International Livestock Research Institute, 2019)
The Feed the Future Innovation Lab for Small Scale Irrigation (ILSSI) is working with Ethiopian farmers to explore options for irrigating fodder that supports enhanced livestock production.